COMPARISON OF THE ELIMINATOR OF THE STATUTE OF PREMEDITATED MURDER IN THE INDONESIAN AND GERMAN CRIMINAL LEGAL SYSTEMS - Binti Nur Farida; Emi Puasa Handayani; Siciliya Mardian Yoel (LPPM STIH Putri Maharaja, 2025)
Expiration in law criminal is a restrictive instrument that states the authority of the state to demand the perpetrator's action after a certain term, which is justified on the basis of certainty and the efficiency of law enforcement. However, its implementation of premeditated murder causes problematic Issues in perspective, justice, and protection of the victim's rights. Under the system law, Indonesian criminal law remains in effect, with a maximum penalty of 20 years, as provided in Constitution Number 1 of 2023. In contrast, German criminal law has been deleted and is no longer applicable to murder premeditated with a confirmed characteristic crime, as it cannot fall by time (imprescriptible). Research: This use method is juridical-normative, employing a conceptual, regulatory-legislative, and comparative approach to analyze differences. The results of the study show that arrangements in Indonesia are more certainty-oriented than formal law. At the same time, Germany emphasizes substantive justice and the protection of fundamental rights, including the right to life. Implementation fell short of its crime-prevention potential, hindering access to justice and openness, leading to impunity. Moreover, in the context of development, modern forensic technology can reveal crimes over time. Therefore, it is necessary to reorient the policy and law of Indonesian criminal law towards the deletion of the expired murder premeditated.